Learning tools for pilgrims in preparing hajj essentials / Anis Amira Talib - Talib, Anis Amira (2016)
Pilgrims have difficulties in understanding and remembering the concepts and preparation of hajj. Most of the Hajj supplementary learning materials are less interactive in providing clear understanding the concepts and preparation of Hajj. This research paper proposes suitable solutions to solve the problem where the multimedia element is applied as to make it to be interactive for the pilgrims. This learning tool provides ways on how to prepare the hajj essentials focused on physical preparations, essentials preparations, and the departure day preparations. During time of the departure preparations are focused on registration processes and flows the pilgrims at Alor Setar station. The target users of this courseware are Malaysian Muslim, especially the first timer. This learning tool is developed based on web platform using Unity 2D software which involves two language of scripting such as C Sharp and JavaScript. The development of the learning tools is based on Waterfall model and Gagne’s Nine Event Instruction. This is a preferred choice as a strategic learning in the content of LPPHE. This project also involved evaluation that has been conducted as the Learning Tool for Pilgrims in Preparing Hajj Essentials (LPPHE). The result of total score after doing post-test obviously showed that using this learning tools can helped them in preparing hajj essentials and all of the candidates really enjoy during learning this learning tools.